The Arabidopsis thaliana Poly(ADP-Ribose) Polymerases 1 and 2 Modify DNA by ADP-Ribosylating Terminal Phosphate Residues - Taipakova, Sabira; Kuanbay, Aigerim; Saint-Pierre, Christine; Gasparutto, Didier; Baiken, Yeldar; Groisman, Regina; Ishchenko, Alexander A.; Saparbaev, Murat; Bissenbaev, Amangeldy K. (Frontiers in Cell and Developmental Biology, 2020)
Proteins from the poly(ADP-ribose) polymerase (PARP) family, such as PARP1 and PARP2, use NAD+ as a substrate to catalyse the synthesis of polymeric chains consisting of ADP-ribose units covalently attached to an acceptor molecule. PARP1 and PARP2 are viewed as DNA damage sensors that, upon binding to strand breaks, poly(ADP-ribosyl)ate themselves and nuclear acceptor proteins. The flowering plant Arabidopsis thaliana contains three genes encoding homologues of mammalian PARPs: atPARP1, atPARP2 and atPARP3. Both atPARP1 and atPARP2 contain poly(ADP-ribosyl)ating activity; however, it is unknown whether they could covalently modify DNA by ADP-ribosylating the strand break termini. Here, we report that similar to their mammalian counterparts the plant atPARP1 and atPARP2 proteins ADP-ribosylate 5'-terminal phosphate residues in duplex DNA oligonucleotides and plasmid containing at least two closely spaced DNA strand breaks. AtPARP1 preferentially catalyses covalent attachment of ADP-ribose units to the ends of recessed DNA duplexes containing 5'-phosphate. Whereas, atPARP2 preferentially ADP-ribosylates the nicked and gapped DNA duplexes containing terminal 5'-phosphate. Similar to their mammalian counterparts, the plant PARPs catalysed DNA ADP-ribosylation is particularly sensitive to the distance that separates two strand breaks in the same DNA molecule, 1.5 and 1 or 2 turns of helix for atPARP1 and atPARP2, respectively. PAR glycohydrolase (PARG) restored native DNA structure by hydrolysing the PAR-DNA adducts generated by atPARPs. Biochemical and mass spectrometry analyses of the PAR-DNA adducts showed that atPARPs utilise phosphorylated DNA termini as an alternative to protein acceptor residues to catalyse PAR chain synthesis via phosphodiester bond formation between C1' of ADP-ribose and a phosphate residue of the terminal nucleotide in DNA fragment. Taken together, these data establish the presence of new type of DNA modifying activity in Arabidopsis PARPs suggesting a possible role of DNA ADP-ribosylation in the DNA damage signaling and repair of terrestrial plants.